The Effectiveness of Geogebra’s Metacognitive Guidance to Develop Critical Thinking Skills - Heris Hendriana; Wahyu Setiawan; Usman Aripin (International Journal on Emerging Mathematics Education, 2019)
This research is a quasi-experimental study aiming at analyzing the role of the metacognitive guidance approach in order to improve high-school students' critical thinking skills by applying  Non-Equivalent Control Group Design. This study involved high school students in one of the high schools in the city of Cimahi. In this study, the pretest for mathematical critical thinking skills is administered to two classes of students of control and experiment groups. The experimental group uses the metacognitive guidance approach assisted by GeoGebra software, whereas the control group uses the conventional method. Both classes receive the same hours of study, mathematics teacher as well as mathematics contents. The researcher conducted observations only in the experimental class. At the end of the treatment, a post-test for the two groups was carried out regarding students’ mathematical critical thinking skills included processing the results of the test, namely the data. After this research has been carried out, the next step is to analyze the data and draw conclusions of the research. In analyzing the data, it is categorized into three levels, namely high, medium and low abilities.  The data is analyzed by means of t-test to test the difference of two means of students’ critical thinking ability. Data analysis was performed using the SPSS software. The analysis shows that there is a significant difference in mathematics critical thinking ability between the two groups of students.